PENERAPAN PENDEKATAN COOPERATIVE LEARNING TIPE JIGSAW UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA DI SDN 001 KEMPAS JAYA - Nenri Budiati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Jigsaw is a type of cooperative learning model that consists of several members in one group who are responsible for mastering the learning material and can teach the material to other members of the group. This article discusses students’ activities and learning outcomes through a cooperative learning model with the Jigsaw model. The research used was Classroom Action Research (CAR) using the Kemmis and Mc. Taggart. The research was conducted at SDN 001 Kempas Jaya. The population of the research was fifth-grade students with a number of 21 students, which consisted of 9 male and 12 female students. The research used quantitative data analysis. Descriptive statistical data collection techniques were carried out through observations, interviews, and evaluation tests at the end of the cycle. Students learning activities increased every cycle. In the pre-cycle, the criteria for students’ activity were 33.33%. After applying jigsaw as a cooperative learning model, it showed an increase. The criteria for students’ activity in cycle I was 61.90% and in cycle II students’ activity was 90.47%, which was active to follow the learning process.